Pengaruh Inklusivitas Gender, Keterlibatan Karyawan, dan Dukungan Sosial Terhadap Kinerja Karyawan dengan Psychological Safety Sebagai Variabel Intervening pada PT. Intan Timur Energi - Kautsar, Careen Adhania; Riyanto, Asis; Mujanah, Siti; Fianto, Achmad Yanu Alif (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyse the effect of gender inclusiveness, employee engagement, and social support on employee performance at PT Intan Timur Energi, with psychological safety as a mediating variable. In the context of globalisation and increasingly complex digitalisation, effective human resource management is very important. Gender inclusiveness in the workplace is proven to increase innovation and team effectiveness, while employee engagement acts as an indicator of successful HR management. Social support from superiors and co-workers also contributes to employees' emotional well-being. This study uses a quantitative approach with an explanatory design to test the relationship between variables. The analysis results show that all independent variables have a positive influence on employee performance, and psychological safety serves as a significant mediator. The findings contribute to the HR management literature as well as practical recommendations for companies in creating an inclusive and productive work environment. It is hoped that this research can serve as a reference for the development of better management strategies in the future.